Predictive Power of the Black & Scholes Option Pricing Model in Pricing FTSE 100 Index Options - Valkama, Veli-Matti (My University, 2007)
The purpose of this study is to examine how well the traditional Black & Scholes option pricing model works. The ability of this in year 1973 published option pricing model to explain observed premiums on FTSE 100 Index options is subjected to four different tests. The empirical part of this study contains the use of the Black & Scholes model in order to calculate the theoretical option prices. The hypotheses are based to the assumptions and predictions of the Black & Scholes model and they are tested with the put-call parity test, the implied volatility test, the smile test and the pricing error test. The data set of this study contains 23,514 FTSE 100 option records from 2 January 2002 to 30 December 2003. These options are traded in the London International Financial Futures and Options Exchange (LIFFE). The empirical test results show that implied volatilities of put options are regularly above the equivalent calls and the difference between implied volatilities is considerable. Against the Black & Scholes model predictions the implied volatility is a biased forecast of actual volatility. Also a volatility smile is found in the implied volatilities and finally the pricing error test shows a significant mispricing behaviour in short-maturity FTSE 100 call options.
Keywords: Black & Scholes; option pricing; implied volatility; put-call parity; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|